2016
DOI: 10.1111/fcp.12199
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline targets nonsmall cell lung cancer through inhibition of mitochondrial function

Abstract: Nonsmall cell lung cancer (NSCLC) is the most common type of lung cancer with a high mortality rate and still remains therapeutically a challenge. A strategy to target NSCLC is to identify agents that are effective against NSCLC cells while sparing normal cells. We show that tigecycline, an FDA-approved antibiotic drug, preferentially targets NSCLC cells. Tigecycline is effective in inhibiting proliferation and inducing apoptosis of multiple cell lines derived from two common NSCLC subtypes: adenocarcinoma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
2
41
1
Order By: Relevance
“…In addition, our studies also add NPC to the growing list of artesunate‐targeted cancers. Various FDA‐approved drugs have been recently identified to be a potential anticancer candidate, such as tigecycline . In lines with these efforts, our work demonstrates the in vitro and in vivo efficacy of artesunate on NPC.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, our studies also add NPC to the growing list of artesunate‐targeted cancers. Various FDA‐approved drugs have been recently identified to be a potential anticancer candidate, such as tigecycline . In lines with these efforts, our work demonstrates the in vitro and in vivo efficacy of artesunate on NPC.…”
Section: Discussionsupporting
confidence: 72%
“…Apart from its anti-leukemic effect, recent studies have demonstrated that TIG could target multiple cancers by impairing mitochondrial functions (Lamb et al, 2015). For example, Jia et al (2016) found that TIG could significantly reduce growth and induce apoptosis in various NSCLC cell lines through inhibition of mitochondrial function. Inhibiting the mitochondrial gene expression and translation pathway by TIG could induce MYC oncogene-dependent tumor cell death, including the osteosarcomas (Oran et al, 2016) and lymphomas (D’Andrea et al, 2016).…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%
“…Previously, we also found that tigecycline inhibited cell metastasis in melanoma via blocking the EMT . Tigecycline was shown to induce intrinsic caspase‐dependent apoptosis in ALL, retinoblastoma, cervical squamous cell carcinoma and NSCLC . However, tigecycline did not cause significant apoptosis in PDAC cells when tigecycline was used alone.…”
Section: Discussionmentioning
confidence: 82%
“…Initially, tigecycline was shown to impair mitochondrial translation in AML, renal cell carcinoma and B‐cell lymphoma . Besides, tigecycline inhibited mitochondrial oxidative phosphorylation to restrict energy and/or oxidative stress and damage in chronic myeloid leukaemia stem cells, acute lymphoblastic leukaemia (ALL), non–small‐cell lung cancer (NSCLC) and hepatocellular carcinoma . However, tigecycline might have other targets in the cells except for proteins in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation